CRITICAL FACTORS FOR E-GOVERNMENT TOWARDS SUSTAINABLE DEVELOPMENT - Ban Qasim Al nidawy; Balqees Naji Ajel; Mohammed Shakour Ahmed (Scholars Digest Publishing, 2023)
The current research aims to verify the impact of the critical factors of e-government towards sustainable development by reviewing some practices and a number of related studies. The study discovered that five factors affect the promotion of sustainable development, namely (legalizing electronic transactions, relying on digital technology, effective organization of government institutions, cooperation between digital technologies and resource management, and citizen satisfaction with e-government). In order to achieve the objective of the research, a major measurement tool was initiated by layout a reconnaissance and allotting it to a sample of workers in the General Directorate of Passports in Baghdad - Al-Rusafa to arrive at the required results through the use of the statistical software (SPSS.V.25), in order to determine the relationship between the study variables, the electronic government with its critical factors. and sustainable development in its dimensions (environmental, social, and economic). The study's findings proved the existence of an active role for the critical factors of e-government in sustainable development, and this indicates that these factors have a fundamental role in promoting sustainable development.
Keywords: E-government, sustainable development, e-government factors to promote sustainable development.